Praising the police, avoiding the station: gendered differences on police–Public relations in Kuwait - AlSabah, Nasser; Aris, Kieren; Nembhard, Susan; Al-Rasheed, Malak (Frontiers in Sociology, 2025)
IntroductionWomen's engagement with key public institutions in the Middle East remains deeply shaped by patriarchal social structures, particularly within the male-dominated criminal justice system. While this dynamic is broadly acknowledged, its implications for police–community relations remain underexplored in empirical research. This study addresses this gap by examining how gender influences public perceptions of, and willingness to cooperate with, the police in Kuwait—a context where cultural norms and institutional hierarchies continue to shape women's interactions with law enforcement.MethodsData were drawn from a nationally representative survey conducted by Kuwait's National Police, encompassing responses from 1,050 members of the public. The analysis assessed how gender influences three central outcomes: (1) trust in the police, (2) perceptions of officer behavior, and (3) willingness to cooperate with law enforcement. Both bivariate and multivariate statistical techniques were employed to detect significant differences and correlates across gender, while controlling for demographic variables such as age, marital status, and educational background.ResultsBivariate analyses revealed a striking paradox: women reported more favorable evaluations of police behavior than men, yet demonstrated significantly lower willingness to cooperate with law enforcement. Subsequent multivariate models confirmed that age, marital status, and education were significant predictors of women's attitudes toward the police. These findings indicate that social and cultural dynamics—beyond gender alone—substantially influence women's perceptions and behaviors within the justice system.Discussion and conclusionThis study offers the first quantitative evidence from the Middle East illustrating how gender inequality shapes police–community relations. Women's comparatively positive assessments of police conduct, coupled with their greater reluctance to cooperate, reveal a deeper tension embedded within patriarchal norms that limit women's agency and engagement with formal institutions. These results underscore the need for gender-sensitive policing strategies and institutional reforms aimed at enhancing women's trust and participation in the justice process. Policymakers and reform advocates should draw on these insights to strengthen women's empowerment, civic confidence, and equitable access to justice across the region. Future research should expand this inquiry by investigating additional cultural and institutional mechanisms that facilitate or impede women's meaningful inclusion in law enforcement interactions.